Development of correlations for overall gas hold-up, volumetric mass transfer coefficient, and effective interfacial area in bubble column reactors using hybrid genetic algorithm-support vector regression technique: viscous newtonian and non-newtonian liq - Gupta, Prashant P.; Merchant, Shamel S.; Bhat, Akshay U.; Gandhi, Ankit B.; Bhagwat, Sunil S.; Joshi, Jyeshtharaj B.; Jayaraman, Valadi K.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2009)
The objective of this study was to develop hybrid genetic algorithm-support vector regression (GA-SVR)-based correlations for overall gas hold-up (epsilon(G)), volumetric mass-transfer coefficient (kt,a), and effective interfacial area (a) in bubble Column reactors for gas-liquid systems employing Viscous Newtonian and non-Newtonian systems as the liquid phase. The hybrid GA-SVR is a novel technique based on the feature 0 generation approach using genetic algorithm (GA). In the present study, GA has been used for nonlinear rescaling of attributes. These, exponentially scaled, are eventually subjected to SVR training The technique is an extension of conventional SVR technique, showing relatively enhanced results For this purpose an extensive literature search was done. From the published literature, 1629 data points for viscous Newtonian and 845 data points for VISCOUS non-Newtonian systems for cc;, 500 data points for viscous Newtonian and 556 data points for viscous non-Newtonian systems for k(L)a, and 208 data points for viscous non-Newtonian systems for a, respectively, were collected These data sets were collected spanning the years 1965-2007 Correlations were developed after taking into account all the parameters affecting epsilon(G), k(1)a, and a such as column and sparger geometry, gas-liquid properties, operating temperature, pressure, and Superficial gas and liquid velocities. The correlations thus developed gave prediction accuracies of 0.994 and 0.999 and average absolute relative errors (AARE) of 3.75 and 1.65% for viscous Newtonian and non-Newtonian systems for epsilon(G), prediction accuracies of 0.983 and 0.998 and AARE of 8 62 and 1.91% for viscous Newtonian and non-Newtonian systems for k(1)a, and prediction accuracy of 0.999 and AARE of 1% for viscous non-Newtonian systems for a, respectively. These correlations also showed much improved results when compared with all the existing correlations proposed in literature. To facilitate their usage, all the hybrid GA-SVR-based correlations have been uploaded on the web link http-//wwwesnips.com/web/UICT-NCL.

Flow and heat transfer in serpentine channels - Karale, Chaitanya M.; Bhagwat, Sunil S.; Ranade, Vivek V. (Aiche Journal, 2013)
Serpentine channels are often used in microchannel reactors and heat exchangers. These channels offer better mixing, higher heat and mass-transfer coefficients than straight channels. In the present work, flow and heat transfer experiments were carried out with a serpentine channel plate comprising of 10 units (single unit dimensions: 1 x 1.5 mm(2) in cross section, length 46.28 mm, D-h 1.2 mm) in series. Pressure drop and heat-transfer coefficients were experimentally measured. Flow and heat transfer in the experimental set-up were simulated using computational fluid dynamics (CFD) models to understand the mechanisms responsible for performance enhancement. The CFD methodology, thus, developed was applied to understand the effect of various geometrical parameters on heat transfer enhancement. A criterion was defined for evaluation of heat transfer performance (heat transfer per unit pumping power), thus, ensuring due considerations to required pumping power. The effect of geometrical parameters and the corresponding mechanisms contributing for enhancement are discussed briefly. Based on the results, a design map comprising different serpentine channels showing heat transfer enhancement with pumping power was developed for Reynolds number of 200 which will be useful for further work on flow and heat transfer in serpentine channels. (C) 2012 American Institute of Chemical Engineers AIChE J, 59: 1814-1827, 2013
Keywords: computational fluid dynamics; heat transfer; pressure drop; serpentine

Improvement of regenerative rankine cycle using absorption heat boosters - Mali, Nilesh A.; Mudadi, Rohit H.; Bhagwat, Sunil S. (International Journal of Exergy, 2013)

Microbial oxidation of medium chain fatty alcohol in the synthesis of sophorolipids by candida bombicola and its physicochemical characterization - Pulate, Vrushali Dengle; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2013)
Sophorolipids (SL) are glycolipid biosurfactants abundantly produced from different feedstocks by yeasts and have been widely developed for various applications. The amphipathic structures of sophorolipids imparts to them surfactant type properties. These biosurfactants are readily isolated in high yield and are nontoxic and biodegradable, which make them industrially interesting as surfactants or emulsifiers. Sophorolipid production was carried out using glucose as a hydrophilic source and lauryl alcohol C12-14, as a hydrophobic source by Candida bombicola (ATCC 22214). Process economics and environmental attractiveness was increased by using a low cost substrate. Optimization studies were carried out where the effect of glucose concentration, pH, temperature and metal ions on sophorolipid production was studied. Optimum production of sophorolipid obtained using lauryl alcohol (SLLA) was achieved after 96 h, the initial pH of the medium was 6.0 with 10 % glucose at 30 A degrees C. Primary characterization of SLLA was done by FTIR. The SLLA showed high physicochemical properties in terms of the surface activities when compared with synthetic surfactants including dodecyl tetraethylene glycol ether and sodium lauryl sulfate. The surface tension of SLLA thus obtained was found to be 24 mN/m with a critical micellar concentration (CMC) value of 0.68 mg/L. Antimicrobial testing showed that SLLA have potent antimicrobial activity against both gram negative bacteria, Escherichia coli (ATCC 8739) and gram positive cocci, Staphylococcus aureuss (ATCC 2079).
Keywords: Biosurfactants; Candida bombicola; CMC; Lauryl alcohol C12-14; sophorolipids; Surface tension

Antimicrobial and SEM studies of sophorolipids synthesized using lauryl alcohol - Dengle-Pulate, Vrushali; Chandorkar, Parul; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2014)
In recent years, researchers have developed biosurfactants for industrial, pharmaceutical and medical applications revealing the promising biological activities of these biomolecules. One of the best studied microbial surfactants are glycolipids, especially sophorolipids (SLs) produced by selected non-pathogenic yeast species of Candida. They are biodegradable, non-toxic and are environmentally friendly. Sophorolipid production was carried out using glucose as the hydrophilic source and lauryl alcohol C12-14, as the hydrophobic source using Candida bombicola ATCC 22214. Primary characterization of the SL obtained using lauryl alcohol (SLLA) was done by FTIR which depicted the presence of alkyl sophorosides/SLs. Antimicrobial activity testing revealed that SLLA showed complete inhibition against gram negative bacteria, Escherichia coli (ATCC 8739) Pseudomonas aeruginosa (ATCC 9027) at 30 and 1 mu g/ml at a contact time of 2 and 4 h respectively. Whereas for gram positive bacteria Staphylococcus aureus (ATCC 6358), Bacillus subtilis (ATCC 6633), complete inhibition was observed at 6 and 1 mu g/ml respectively at a contact time of 4 h. The formed SLLA showed noteworthy inhibition against the pathogenic yeast Candida albicans (ATCC 2091) at 50 mu g/ml with a contact time of 4 h. These values are remarkably low compared to reported values of oleic acid SLs and linolenic acid SLs which were studied for antimicrobial properties. Scanning electron microscopy analysis of the treated cells revealed the changes in morphology and topography of the microorganisms.
Keywords: Antimicrobial property; Biosurfactants; Candida bombicola; Lauryl alcohol; sophorolipids

Experimental investigation of isothermal vapor-liquid equilibrium and estimation of excess thermodynamic properties (h(E)) of CHO2K-H2O from 278.15 to 423.15 K - Takalkar, Gorakshnath D.; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (Journal of Chemical and Engineering Data, 2019)
In this paper, vapor liquid equilibrium (VLE) of a binary mixture, potassium formate-water (CHO2K-H2O), was measured experimentally using a dynamic moving type VLE setup in the temperature range of 313.15 to 393.15 K. Overall, large vapor pressure data points generated for the mole fraction of CHO2K from 0.023 to 0.461 and the solution temperature up to 423.15 K were used to correlate the local composition-based activity coefficient model (NRTL model). The data obtained via the thermodynamic model fitting shows good agreement with the experimental VLE data with overall average relative deviation of 2.15% and root-mean-square deviation of 0.25%. The obtained results further indicate that the binary mixture exhibits a negative deviation from the Raoult's law, which is an important characteristic of the working fluid used for a heat-activated vapor absorption system (VAS). Therefore, the CHO2K-H2O mixture can be considered as an alternative working pair that will overcome the limitations allied to the crystallization and corrosion of the commercial working fluids mainly lithium bromide-water (LiBr-H2O). The fitted nonrandom two-liquid model was further utilized to determine the excess thermodynamic properties, solution enthalpy, solution entropy, and equilibrium P-T-x (Duhring) plot.

Energetic and exergetic performance of NH3-H2O-based absorption refrigeration cycle: effect of operating factor - Takalkar, Gorakshnath Dadabhau; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (International Journal of Exergy, 2020)
One of the major objectives while designing the vapour absorption refrigeration system (VARS) is to acquire better performance within the accessible heat source and sink temperature limit. In this paper, attempts are made to identify the temperature limit for the optimisation of a single stage ammonia refrigeration system (AAR) by performing a thermodynamic analysis. To estimate the potential of utilisation of low-grade heat energy, operating factor (R) is considered towards optimising the energetic (COP) and exergetic COP (ECOP). The simulated COP and ECOP results are expended to predict the feasibility and optimum operating region for an AAR cycle in terms of theRand various operating temperatures such asT(gen),T-abs,T-cond,T-e. The operating factorRcovers a wide range of applications i.e., from deep-freezing (253.15 K) to air conditioning (283.15 K) and from water-cooling (303.15 K) to air cooling (318.15 K).
Keywords: AAR; ammonia absorption refrigeration; cold storage; exergy; operating factor; solar energy